Fatores politicos condicionantes da criação e desenvolvimento de universidades brasileiras: o caso da Universidade Federal de Rondonia - Leite Neto, Clementino (1993)
This dissertation aims to identify the significant political elements to the Establishment and Development of the Brasilian Universities: the situation of the Fundação Universidade Federal de Rondônia, clarifying the process facing up speech and practice carried out in the establishment of the Institution, as well as in its development processo To that purpose, it was delinested an intensive search for documents concerning the Universidade Federal de Rondônia, particularly speechs and pronouncements maden by politicians and the most important members of the Institution Administrative body. In the end, the resul ts brought out the idea that speech is the key factor in the modelling power process, revealling itself as a social transformation proposal in its main aspects, as the conception of UniversitYi and the social adjustment in its real aspects, as the idea of society, being i ts practices determined basically in a social conformation perspective.